Dendritic cell effector mechanisms and tumor immune microenvironment infiltration define TLR8 modulation and PD-1 blockade - Ruiz-Torres, Daniel A.; Wise, Jillian F.; Zhao, Brian Yinge; Oliveira-Costa, Joao Paulo; Cavallaro, Sara; Sadow, Peter M.; Fang, Jacy; Yilmaz, Osman; Patel, Amar; Loosbroock, Christopher; Sade-Feldman, Moshe; Faden, Daniel L.; et al. (Frontiers in Immunology, 2024)
The potent immunostimulatory effects of toll-like receptor 8 (TLR8) agonism in combination with PD-1 blockade have resulted in various preclinical investigations, yet the mechanism of action in humans remains unknown. To decipher the combinatory mode of action of TLR8 agonism and PD-1 blockade, we employed a unique, open-label, phase 1b pre-operative window of opportunity clinical trial (NCT03906526) in head and neck squamous cell carcinoma (HNSCC) patients. Matched pre- and post-treatment tumor biopsies from the same lesion were obtained. We used single-cell RNA sequencing and custom multiplex staining to leverage the unique advantage of same-lesion longitudinal sampling. Patients receiving dual TLR8 agonism and anti-PD-1 blockade exhibited marked upregulation of innate immune effector genes and cytokines, highlighted by increased CLEC9A+ dendritic cell and CLEC7A/SYK expression. This was revealed via comparison with a previous cohort from an anti-PD-1 blockade monotherapy single-cell RNA sequencing study. Furthermore, in dual therapy patients, post-treatment mature dendritic cells increased in adjacency to CD8+ T-cells. Increased tumoral cytotoxic T-lymphocyte densities and expanded CXCL13+CD8+ T-cell populations were observed in responders, with increased tertiary lymphoid structures (TLSs) across all three patients. This study provides key insights into the mode of action of TLR8 agonism and anti-PD-1 blockade immune targeting in HNSCC patients.